2017
DOI: 10.3906/sag-1505-69
|View full text |Cite
|
Sign up to set email alerts
|

The effect of kisspeptin on spermatogenesis and apoptosis in rats

Abstract: IntroductionKisspeptins, the peptide products of the KiSS-1 gene, bind to the G protein-coupled receptor 54 (GPR54), a critical regulator of GnRH secretion. The N-terminally truncated peptide metastin 45-54 exhibits 10-fold higher receptorbinding affinity than full-length metastin; it also shows agonistic KISS-1R activity (1).Kisspeptins are known to play a role in puberty, cancer metastasis, and vasoconstriction (2,3-7). They are synthesized in the arcuate and anteroventral periventricular hypothalamic neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Experiments in rats have revealed that exogenous kisspeptin administration causes an initial increase in testosterone plasma levels, but this effect vanishes if the treatment is prolonged [102]. These results were in harmony with those of Thompson and colleagues, who proposed the HPG desensitization hypothesis after kisspeptin continuous treatment, previously mentioned in this review [81].…”
Section: Testicular Steroidogenesissupporting
confidence: 87%
“…Experiments in rats have revealed that exogenous kisspeptin administration causes an initial increase in testosterone plasma levels, but this effect vanishes if the treatment is prolonged [102]. These results were in harmony with those of Thompson and colleagues, who proposed the HPG desensitization hypothesis after kisspeptin continuous treatment, previously mentioned in this review [81].…”
Section: Testicular Steroidogenesissupporting
confidence: 87%
“…In this study, higher serum kisspeptin in buffalo bulls with higher sperm concentration hints the link of kisspeptin with spermatogenesis. Various supportive evidences derived from human and laboratory animals exist showed that kisspeptin increased spermatogenic cell proliferation (Ayturk et al, 2017; Selvaraj et al., 2013; Zou et al., 2019). In addition, kisspeptin and GPR54 (kisspeptin receptor) genes were detected on spermatids (Hua, Doran, Kyle, Yeo, & Colledge, 2013) and sperm (Pinto Pérez et al, 2012) in human and mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have supported these observed negative findings. Administration of kp54 (50 nmol/day) for 13 days using mini-osmotic pumps implanted subcutaneously in the interscapular region of male rats significantly decreased serum hormone levels (LH, FSH, and testosterone levels), testis weight, sperm count and motility through direct desensitization of the HPG axis [51].…”
Section: Effects Of Kisspeptin On Testicular Steroidogenesismentioning
confidence: 96%
“…Continuous infusions of kp led to seminiferous tubule degeneration and apoptosis, and reduction in, L.H. ; testosterone and inhibin B levels in mice[50,51].…”
mentioning
confidence: 93%